2018
DOI: 10.1016/j.paid.2018.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Social networking sites addiction and adolescent depression: A moderated mediation model of rumination and self-esteem

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
94
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(106 citation statements)
references
References 46 publications
8
94
0
4
Order By: Relevance
“…Only a few other scholars investigated social media addiction/ social media use and its relationships with depression or other mental health problems; almost all these studies found that social media addiction associated with depression/other mental health problems ( Note. R2 adjusted = 0.179 CI = confidence interval for B Seabrook et al, 2016;Shensa et al, 2018;Wang et al, 2018;Waqas et al, 2018). The young generation (high school students) was the target population in many of these studies; they mostly utilized Goldberg, DASS (Depression Anxiety Stress Scale), CES-D and the 6-item Bergen Social Media Addiction Scale (BSMAS) for measuring depression and social media addiction, while we used IATs and CES-Ds in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few other scholars investigated social media addiction/ social media use and its relationships with depression or other mental health problems; almost all these studies found that social media addiction associated with depression/other mental health problems ( Note. R2 adjusted = 0.179 CI = confidence interval for B Seabrook et al, 2016;Shensa et al, 2018;Wang et al, 2018;Waqas et al, 2018). The young generation (high school students) was the target population in many of these studies; they mostly utilized Goldberg, DASS (Depression Anxiety Stress Scale), CES-D and the 6-item Bergen Social Media Addiction Scale (BSMAS) for measuring depression and social media addiction, while we used IATs and CES-Ds in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Many prior studies have explored the relationship of social media usage with the users' mental health problems (e.g. depression, anxiety, stress, loneliness, and self-esteem) among the various age group of people in developed countries (Glazzard & Stones, 2016;Hou et al, 2019;Savci, 2016;Shensa et al, 2018;Wang et al, 2018;Waqas et al, 2018). In the least developed countries such as Afghanistan, there is not enough relevant academic literature.…”
Section: Introductionmentioning
confidence: 99%
“…According to the latter approach, SNS addiction is viewed as a generic phenomenon (e.g. Tang and Koh 2017;Wang et al 2018). In line with such understanding, impairment associated with Facebook addiction (related for example to higher stress and lower well-being) should also be present in SNS addiction generally.…”
Section: Conceptual and Methodological Perspectives On Sns Addictionmentioning
confidence: 99%
“…Various measures were used to assess SNUD with the authors of studies adapting measures into Chinese/Mandarin and to assess Chinese SNSs (i.e., western SNS name, such as Facebook R , was exchanged for a Chinese SNS name such as WeChat R ). Hou et al (2019) and Wang et al (2018) utilized adapted versions of the Facebook Intrusion Questionnaire (Elphinston and Noller, 2011;Li et al, 2018a,b) used the Online Social Networking Addiction Scale (Li et al, 2016), Liu and Ma (2018a) used the Social Media Addiction Scale (Liu and Ma, 2018b), Chen et al (2019) used the Social Networking Websites Addiction Scale (SNWAS; Turel and Serenko, 2012) and the Social Networking Sites Addiction Tendency Scale (SNSATS; Wilson et al, 2010). (Yam et al, 2019) used the Bergen Social Media Addiction Scale (Andreassen et al, 2012), Li et al (2017) used an adapted version of the Facebook Addiction Scale (Koc and Gulyagci, 2013), and Hong et al (2014) used the Internet Addiction Test (Young, 1996).…”
Section: Methods Of Assessing Social Network Use Disordermentioning
confidence: 99%